Semi-aromatic polyamide resin composition and metal-plated molded article

JP7652079B2Active Publication Date: 2025-03-27TOYOBO MC CORP
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2021561412
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-11-24
Publication Date
2025-03-27
Estimated Expiration
2040-11-24

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、良メッキ性、低吸水性、耐ハンダリフロー性を有する半芳香族ポリアミド樹脂組成物、及びこの半芳香族ポリアミド樹脂組成物を用いたメッキ成形体を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652079000001
    Figure 0007652079000001
  • Figure 0007652079000002
    Figure 0007652079000002
  • Figure 0007652079000003
    Figure 0007652079000003
Patent Text Reader

Abstract

[Problem] To provide a semi-aromatic polyamide resin composition having good platability, low water absorbency, and excellent solder reflow resistance. [Solution] The semi-aromatic polyamide resin composition according to the present invention comprises, based on 100 parts by mass of a semi-aromatic polyamide (A), 10-200 parts by mass of an inorganic filler (B) and 2-30 parts by mass of a toughness improver (C). The semi-aromatic polyamide resin (A) satisfies (a) and (b) below. (a) The melting point (Tm) measured by differential scanning calorimetry (DSC) is 280°C or higher, and (b) the equilibrium water absorption at 80°C and 95% RH is 3.5% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a semi-aromatic polyamide resin composition having good plating properties, low water absorption and excellent solder reflow resistance. [Background technology]

[0002] Taking advantage of their excellent properties and ease of melt molding, polyamide resins have been used in clothing, industrial fiber, engineering plastics, etc. In recent years, with technological developments in various fields, the uses of polyamide resins have expanded even further, and they are now used in a variety of applications, from automobile parts around the engine to electrical and electronic parts such as smartphones.

[0003] As various technologies advance, the performance of electrical and electronic equipment and office automation equipment is improving. In the automotive industry, for example, motors are used as driving sources, and there is a need to reduce the impact that electromagnetic waves generated from various components have on surrounding parts or the human body.

[0004] In order to address these issues, studies have been conducted to impart electromagnetic shielding properties to the components of various devices, and metals with excellent electromagnetic shielding properties and resins containing conductive fillers have been used. Although it is possible to achieve electromagnetic shielding using these methods, there are still issues with regard to improving automobile fuel efficiency, reducing the weight of products, and resin processability.

[0005] On the other hand, metal deposition or metal plating on the surface of resin molded products is known as a method for imparting electromagnetic shielding properties to component parts of equipment. This method is used in various fields because it is easier to reduce the weight of the parts than to make them out of metal, and it can also provide sufficient electromagnetic shielding properties.

[0006] Various metal deposition and metal plating techniques for resins have been developed. Patent Document 1 discloses a polyamide resin composition that is made of polyamide, an inorganic filler, and a modified styrene-olefin copolymer and has excellent adhesion properties to metal plating. However, the polyamide resin composition described in the document has a melting point lower than 280°C, and therefore is difficult to withstand the solder reflow process used in the manufacture of base components.

[0007] Patent Document 2 discloses a resin composition for metal deposition containing a polyamide resin, a styrene-based resin, and a filler. However, the resin composition for metal deposition described in this document describes good adhesion to a metal film formed by a metal deposition technique, and the metal film formation process is essentially different from that of the metal plating technique of the present invention. In addition, all of the resin compositions for metal deposition described in the examples have melting points lower than 280°C, making it difficult to withstand the solder reflow process.

[0008] Patent Document 3 discloses a resin composition for forming a plating layer, which contains a semi-aromatic polyamide composed of terephthalic acid and a diamine component having an alkylene group having 4 to 25 carbon atoms, and an inorganic filler. However, the resin composition described in this document does not mention the effect of further improving plating adhesion by using a toughness improver.

[0009] Patent Document 4 discloses a molded article having a metal layer on the surface thereof, which is obtained from a polyamide resin composition comprising a polyamide resin composed of terephthalic acid and 1,9-nonanediamine and a filler. However, the resin composition described in this document is limited to a polyamide resin.

[0010] Patent Document 5 discloses a method for forming an electroless plating layer using a resin composition in which a filler is mixed with a semi-aromatic polyamide resin selected from polyamide 10T, polyamide 9T, polyamide 6T, polyamide 4T, or polyphthalamide. However, the technique described in this document has limitations in terms of equipment, since it is necessary to set the mold temperature to 180 to 240°C when molding a base to be plated using the resin composition.

[0011] As described above, although various inventions have been made regarding metal vapor deposition and metal plating on resin, various problems and limitations remain. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] Special Publication No. 8-11782 [Patent Document 2] JP 2006-131821 A [Patent Document 3] Patent No. 3009707 [Patent Document 4] Patent No. 3400133 [Patent Document 5] Patent No. 6190154 Summary of the Invention [Problem to be solved by the invention]

[0013] The present invention has been made in view of the current state of the prior art, and an object of the present invention is to provide a semi-aromatic polyamide resin composition which has good plating properties, low water absorption and excellent solder reflow resistance.

[0014] In order to achieve the above object, the present inventors have thoroughly investigated the composition of the semi-aromatic polyamide resin, as well as the types and amounts of fillers and toughness improvers, and as a result have been able to provide a semi-aromatic polyamide resin composition that has good plating properties, low water absorption and excellent solder reflow resistance.

[0015] That is, the present invention has the following configuration. (1) A semi-aromatic polyamide resin composition comprising 10 to 200 parts by mass of an inorganic filler (B) and 2 to 30 parts by mass of a toughness improver (C) per 100 parts by mass of a semi-aromatic polyamide (A), wherein the semi-aromatic polyamide resin (A) satisfies the following (a) and (b): (a) A melting point (Tm) of 280°C or higher as measured by differential scanning calorimetry (DSC) (b) 80℃95%RH equilibrium water absorption is 3.5% or less (2) The semi-aromatic polyamide resin composition according to (1), wherein the toughness improver (C) is at least one selected from the group consisting of olefin-based copolymers and styrene-based elastomers. (3) The semi-aromatic polyamide resin composition according to (2), wherein the olefin-based copolymer is at least one selected from the group consisting of (ethylene and / or propylene)·α-olefin-based copolymers and (ethylene and / or propylene)·(α,β-unsaturated carboxylic acid and / or unsaturated carboxylic acid ester)-based copolymers. (4) The semi-aromatic polyamide resin composition according to (2) or (3), wherein the styrene-based elastomer is a styrene-ethylene-butylene-styrene block copolymer. (5) The semi-aromatic polyamide resin composition according to any one of (1) to (4), wherein the inorganic filler (B) contains an aluminum silicate or a calcium silicate. (6) A metal-plated molded article using the semi-aromatic polyamide resin composition according to any one of (1) to (5). Effect of the Invention

[0016] According to the present invention, it is possible to provide a semi-aromatic polyamide resin composition having good plating properties, low water absorption and solder reflow resistance, and a plated molded article using this semi-aromatic polyamide resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The semi-aromatic polyamide resin composition of the present invention will be described below.

[0018] The semi-aromatic polyamide resin (A) used in the present invention is not particularly limited, and is a semi-aromatic polyamide having an acid amide bond (-CONH-) and an aromatic ring (benzene ring) in the molecule. Examples of semi-aromatic polyamides include 6T-based polyamides (e.g., polyamide 6T / 6I consisting of terephthalic acid / isophthalic acid / hexamethylenediamine, polyamide 6T / 66 consisting of terephthalic acid / adipic acid / hexamethylenediamine, polyamide 6T / 6I / 66 consisting of terephthalic acid / isophthalic acid / adipic acid / hexamethylenediamine, polyamide 6T / M-5T consisting of terephthalic acid / hexamethylenediamine / 2-methyl-1,5-pent ... Examples include polyamide 6T / 6 made of samethylenediamine / ε-caprolactam, polyamide 6T / 4T made of terephthalic acid / hexamethylenediamine / tetramethylenediamine, 9T polyamide (terephthalic acid / 1,9-nonanediamine / 2-methyl-1,8-octanediamine), 10T polyamide (terephthalic acid / 1,10-decanediamine), 12T polyamide (terephthalic acid / 1,12-dodecanediamine), and polyamide made of sebacic acid / paraxylenediamine.

[0019] The semi-aromatic polyamide resin (A) used in the present invention must have a melting point (Tm) of 280°C or higher as measured by differential scanning calorimetry (DSC). The melting point (Tm) is preferably 285°C or higher, more preferably 290°C or higher. If Tm is below the lower limit, the molded article may melt or deform when the molded article using the semi-aromatic polyamide resin composition of the present invention is processed in a solder reflow process. The upper limit of Tm is preferably 340°C or lower, more preferably 330°C or lower, and even more preferably 320°C or lower. If Tm exceeds the upper limit, the processing temperature during molding becomes extremely high, and there is a possibility that the resin may decompose due to heat. Measurement by differential scanning calorimetry (DSC) will be described in the following Examples section.

[0020] The semi-aromatic polyamide resin (A) used in the present invention must have an equilibrium water absorption rate at 80°C and 95% RH of 3.5% or less, measured by the method described in the Examples section below. The equilibrium water absorption rate at 80°C and 95% RH is preferably 3.0% or less. If the equilibrium water absorption rate at 80°C and 95% RH exceeds the upper limit, when a molded product using such a semi-aromatic polyamide resin composition is processed in a solder reflow process, swelling of the molded product surface may occur due to the expansion of moisture in the molded product, and assembly defects may occur due to dimensional changes in the molded product.

[0021] From the viewpoints of Tm and equilibrium water absorption at 80° C. and 95% RH, the semi-aromatic polyamide resin (A) used in the present invention is preferably the following semi-aromatic polyamide resin. The semi-aromatic polyamide resin (A) is preferably a semi-aromatic polyamide resin containing 50 to 100 mol % of repeating units composed of a diamine having 6 to 12 carbon atoms and terephthalic acid, and 0 to 50 mol % of repeating units composed of an aminocarboxylic acid having 10 or more carbon atoms or a lactam having 10 or more carbon atoms, more preferably a semi-aromatic polyamide resin containing 50 to 98 mol % of repeating units composed of a diamine having 6 to 12 carbon atoms and terephthalic acid, and 2 to 50 mol % of repeating units composed of an aminocarboxylic acid having 10 or more carbon atoms or a lactam having 10 or more carbon atoms, and even more preferably a semi-aromatic polyamide resin containing 55 to 98 mol % of repeating units composed of a diamine having 6 to 12 carbon atoms and terephthalic acid, and 2 to 45 mol % of repeating units composed of an aminocarboxylic acid having 10 or more carbon atoms or a lactam having 10 or more carbon atoms. If the proportion of repeating units consisting of a diamine having 6 to 12 carbon atoms and terephthalic acid in the semi-aromatic polyamide resin (A) is less than 50 mol%, the molded article may melt or deform during the solder reflow process due to a decrease in Tm. On the other hand, in order to appropriately improve the Tm of the semi-aromatic polyamide resin (A), it is more preferable to set the proportion of repeating units consisting of a diamine having 6 to 12 carbon atoms and terephthalic acid in the semi-aromatic polyamide resin (A) to 55 mol% or more, and even more preferably 60 mol% or more.

[0022] Examples of the diamine component having 6 to 12 carbon atoms constituting the semi-aromatic polyamide resin (A) include 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 2-methyl-1,8-octamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, 1,12-dodecamethylenediamine, etc. These may be used alone or in combination.

[0023] As the aminocarboxylic acid having 10 or more carbon atoms or the lactam having 10 or more carbon atoms constituting the semi-aromatic polyamide resin (A), an aminocarboxylic acid or lactam having 11 to 18 carbon atoms is preferred. Among them, 11-aminoundecanoic acid, undecane lactam, 12-aminododecanoic acid, and 12-lauryllactam are preferred. From the viewpoint of Tm and 80°C 95% RH equilibrium water absorption, it is preferred that one or more of aminocarboxylic acids having 11 to 18 carbon atoms or lactams having 11 to 18 carbon atoms are copolymerized as the copolymerization component.

[0024] The semi-aromatic polyamide resin (A) used in the present invention can be copolymerized with other components in an amount of 50 mol % or less in the constituent units. Examples of copolymerizable diamine components include aliphatic diamines such as 1,13-tridecamethylenediamine, 1,16-hexadecamethylenediamine, 1,18-octadecamethylenediamine, and 2,2,4 (or 2,4,4)-trimethylhexamethylenediamine, alicyclic diamines such as piperazine, cyclohexanediamine, bis(3-methyl-4-aminohexyl)methane, bis-(4,4'-aminocyclohexyl)methane, and isophoronediamine, and aromatic diamines such as metaxylylenediamine, paraxylylenediamine, paraphenylenediamine, and metaphenylenediamine, and hydrogenated products thereof.

[0025] Examples of the copolymerizable acid component include aromatic dicarboxylic acids such as isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 2,2'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 5-sodium sulfonate isophthalic acid, and 5-hydroxyisophthalic acid; and aliphatic or alicyclic dicarboxylic acids such as fumaric acid, maleic acid, succinic acid, itaconic acid, adipic acid, azelaic acid, sebacic acid, 1,11-undecanedioic acid, 1,12-dodecanedioic acid, 1,14-tetradecanedioic acid, 1,18-octadecanedioic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, and dimer acid. Furthermore, examples of copolymerizable components include ε-caprolactam.

[0026] The aromatic polyamide resin (A) used in the present invention is preferably a semi-aromatic polyamide resin containing 50 to 100 mol % of repeating units consisting of hexamethylenediamine and terephthalic acid and 0 to 50 mol % of repeating units consisting of aminoundecanoic acid or undecane lactam, and is preferably a semi-aromatic polyamide resin containing 50 to 98 mol % of repeating units consisting of hexamethylenediamine and terephthalic acid and 2 to 50 mol % of repeating units consisting of aminoundecanoic acid or undecane lactam. It is more preferable that the polyamide resin is a semi-aromatic polyamide resin containing 55 to 80 mol % of repeating units composed of hexamethylenediamine and terephthalic acid and 20 to 45 mol % of repeating units composed of aminoundecanoic acid or undecane lactam, and it is even more preferable that the polyamide resin is a semi-aromatic polyamide resin containing 60 to 70 mol % of repeating units composed of hexamethylenediamine and terephthalic acid and 30 to 40 mol % of repeating units composed of aminoundecanoic acid or undecane lactam. If the ratio of the repeating units consisting of hexamethylenediamine and terephthalic acid in the semi-aromatic polyamide resin (A) is less than 50 mol%, the molded article may melt or deform during the solder reflow process due to a decrease in Tm. On the other hand, by setting the ratio of the repeating units consisting of hexamethylenediamine and terephthalic acid in the semi-aromatic polyamide resin (A) to 55 to 80 mol%, it is possible to control the crystallinity and molecular mobility of the semi-aromatic polyamide resin (A) and appropriately improve Tm, which is more preferable. Furthermore, by setting the proportion of repeating units consisting of hexamethylenediamine and terephthalic acid in the semi-aromatic polyamide resin (A) to 60 to 70 mol % and the proportion of repeating units consisting of aminoundecanoic acid or undecanelactam used as a copolymerization component to 30 to 40 mol %, it is possible to set Tm in the range of 300°C to 320°C, which not only facilitates molding process but also makes it possible to reduce the 80°C / 95% RH equilibrium water absorption to 3.5% or less, thereby providing excellent solder reflow resistance, which is even more preferable.

[0027] Examples of catalysts used in producing the semi-aromatic polyamide resin (A) include phosphoric acid, phosphorous acid, hypophosphorous acid, or their metal salts, ammonium salts, and esters. Specific examples of metal species of metal salts include potassium, sodium, magnesium, vanadium, calcium, zinc, cobalt, manganese, tin, tungsten, germanium, titanium, and antimony. Examples of esters include ethyl ester, isopropyl ester, butyl ester, hexyl ester, isodecyl ester, octadecyl ester, decyl ester, stearyl ester, and phenyl ester. In addition, from the viewpoint of improving melt retention stability, it is preferable to add an alkali compound such as sodium hydroxide, potassium hydroxide, or magnesium hydroxide.

[0028] The relative viscosity (RV) of the semi-aromatic polyamide resin (A) measured in 96% concentrated sulfuric acid at 20° C. is preferably 0.4 to 4.0, more preferably 1.0 to 3.0, and even more preferably 1.5 to 2.5. Methods for adjusting the relative viscosity of the polyamide within a certain range include a method for adjusting the molecular weight.

[0029] The terminal carboxyl group concentration and terminal amino group concentration of the semi-aromatic polyamide resin (A) are preferably 0 to 200 eq / ton and 0 to 100 eq / ton, respectively. If the terminal carboxyl group concentration and terminal amino group concentration exceed 200 eq / ton, gelation or deterioration may be promoted during molding.

[0030] The amount of terminal groups and the molecular weight of the semi-aromatic polyamide resin (A) can be adjusted by a method of polycondensation in which the molar ratio of the amount of amino groups to the amount of carboxyl groups is adjusted, or a method of adding a terminal blocking agent.

[0031] The timing of adding the end-capping agent may include the time of charging the raw materials, the start of polymerization, the later stage of polymerization, or the end of polymerization. The end-capping agent is not particularly limited as long as it is a monofunctional compound that is reactive with the amino group or carboxyl group at the polyamide terminal, and may include monocarboxylic acids or monoamines, acid anhydrides such as phthalic anhydride, monoisocyanates, monoacid halides, monoesters, and monoalcohols. Examples of the end-capping agent include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexylcarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid; acid anhydrides such as maleic anhydride, phthalic anhydride, and hexahydrophthalic anhydride; aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; and aromatic monoamines such as aniline, toluidine, diphenylamine, and naphthylamine.

[0032] The semi-aromatic polyamide resin (A) can be produced by a conventional method, and can be easily synthesized, for example, by subjecting raw material monomers to a co-condensation reaction. The order of the co-condensation polymerization reaction is not particularly limited, and all raw material monomers may be reacted at once, or some raw material monomers may be reacted first, followed by the remaining raw material monomers. The polymerization method is not particularly limited, and may proceed in a continuous process from raw material charging to polymer preparation, or an oligomer may be prepared once and then polymerized in a separate process using an extruder, or the oligomer may be polymerized by solid-phase polymerization. The ratio of each structural unit in the synthesized copolymerized polyamide can be controlled by adjusting the charging ratio of the raw material monomers.

[0033] The inorganic filler (B) used in the present invention is blended to improve the metal plating adhesion, strength, and dimensional stability of the semi-aromatic polyamide resin composition, and at least one selected from fibrous fillers and non-fibrous fillers is used. Examples of fibrous fillers include glass fibers, carbon fibers, boron fibers, ceramic fibers, metal fibers, potassium titanate whiskers, aluminum borate whiskers, zinc oxide whiskers, calcium carbonate whiskers, magnesium sulfate whiskers, and fibrous wollastonite. Examples of non-fibrous fillers include aluminum silicate salts (kaolin), calcium silicate salts (wollastonite), magnesium silicate salts (talc), mica, calcium carbonate, barium sulfate, glass beads, and glass balloons. In addition, the inorganic filler (B) preferably contains at least one selected from aluminum silicate salts and calcium silicate salts as a main component, and more preferably contains aluminum silicate salts as a main component. Aluminum silicate salts have excellent appearance when molded, and because they do not dissolve in the etching solution used in the plating process, they are easy to create unevenness and have excellent plating adhesion. These can be used not only alone, but also in combination of several types.

[0034] In order to improve the affinity with the semi-aromatic polyamide resin (A), the inorganic filler (B) is preferably treated with an organic agent or a coupling agent. Alternatively, it is preferable to use a coupling agent in combination with the inorganic filler (B) during melt compounding. As the coupling agent, any of silane-based coupling agents, titanate-based coupling agents, and aluminum-based coupling agents may be used, and among them, aminosilane coupling agents and epoxysilane coupling agents are particularly preferable.

[0035] An example of a method for metal plating the surface of the semi-aromatic polyamide resin composition of the present invention is to bring an etching solution into contact with the surface of a molded article formed using the semi-aromatic polyamide resin composition, perform etching (surface roughening), form a concave-convex structure on the surface of the molded article, and then metal plating the surface. It is presumed that the concave-convex formed by etching exhibits a mechanical bonding effect, thereby obtaining excellent plating adhesion.

[0036] The amount of the inorganic filler (B) used in the present invention must be 10 to 200 parts by mass relative to 100 parts by mass of the semi-aromatic polyamide resin (A). In addition, it is preferably 10 to 190 parts by mass, more preferably 15 to 180 parts by mass, and even more preferably 20 to 170 parts by mass. If the amount of the inorganic filler (B) is below the lower limit, the unevenness after etching is insufficient, and good plating adhesion may not be achieved. If the amount of the inorganic filler (B) is above the upper limit, the unevenness after etching increases, but molding processability may be reduced. In the semi-aromatic polyamide resin composition of the present invention, the amount of the inorganic filler is the content in the semi-aromatic polyamide resin composition.

[0037] The toughness improver (C) used in the present invention can improve not only the toughness of the semi-aromatic polyamide resin composition but also the metal plating adhesion. The toughness improver is not particularly limited as long as it can improve the toughness of the semi-aromatic polyamide resin composition, and examples thereof include olefin copolymers, elastomers, synthetic rubbers, and natural rubbers.

[0038] Examples of the toughness improver (C) include olefin-based polymers such as olefin-based copolymers and ionomer polymers, elastomers such as styrene-based elastomers, urethane-based elastomers, fluorine-based elastomers, vinyl chloride-based elastomers, polyester-based elastomers, and polyamide-based elastomers, and synthetic rubbers such as thiokol rubber, polysulfide rubber, acrylic rubber, silicone rubber, polyether rubber, and epichlorohydrin rubber. From the viewpoint of compatibility with the semi-aromatic polyamide resin (A) and heat resistance, olefin-based polymers and elastomers are preferred, and olefin-based copolymers and styrene-based elastomers are more preferred. As the olefin-based copolymers, (ethylene and / or propylene)·α-olefin-based copolymers and (ethylene and / or propylene)·(α,β-unsaturated carboxylic acid and / or unsaturated carboxylic acid ester)-based copolymers are preferred. As the styrene-based elastomers, styrene-ethylene-butylene-styrene block copolymers are preferred. These may be used alone or in combination of several types. The toughness improver (C) is particularly preferably at least one of an (ethylene and / or propylene)·α-olefin copolymer and a styrene-ethylene-butylene-styrene block copolymer.

[0039] The (ethylene and / or propylene)·α-olefin copolymer used in the present invention is a polymer obtained by copolymerizing ethylene and / or propylene with an α-olefin having 4 or more carbon atoms. Examples of the α-olefin having 4 or more carbon atoms include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, and 1-octadecene. Examples of suitable ethylene glycol ethers include ethylene glycol ethers, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4,4-dimethyl-1-pentene, 4-ethyl-1-hexene, 3-ethyl-1-hexene, 9-methyl-1-decene, 11-methyl-1-dodecene, 12-ethyl-1-tetradecene, and combinations thereof. Also, 1,4-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,4-octadiene, 1,5-octadiene, 1,6-octadiene, 1,7-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, 4-ethylidene-8-methyl-1,7-nonadiene, 4,8-dimethyl-1,4,8-decatriene (DMDT), dicyclopentadiene, cyclohexadiene, dicyclopentadiene, Polyenes such as non-conjugated dienes, such as octadiene, methylenenorbornene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, and 2-propenyl-2,2-norbornadiene may also be copolymerized.

[0040] The (ethylene and / or propylene)·(α,β-unsaturated carboxylic acid and / or unsaturated carboxylic acid ester) copolymer is a polymer obtained by copolymerizing ethylene and / or propylene with an α,β-unsaturated carboxylic acid and / or an unsaturated carboxylic acid ester monomer. Examples of the α,β-unsaturated carboxylic acid monomer include acrylic acid and methacrylic acid, and examples of the α,β-unsaturated carboxylic acid ester monomer include the methyl ester, ethyl ester, propyl ester, butyl ester, pentyl ester, hexyl ester, heptyl ester, octyl ester, nonyl ester, decyl ester, etc. of these unsaturated carboxylic acids, or mixtures thereof.

[0041] An ionomer polymer is a copolymer of an olefin and an α,β-unsaturated carboxylic acid in which at least a part of the carboxyl groups is ionized by neutralization with a metal ion. The olefin is preferably ethylene, and the α,β-unsaturated carboxylic acid is preferably acrylic acid or methacrylic acid, but is not limited to the above examples, and an unsaturated carboxylic acid ester monomer may be copolymerized. In addition, examples of the metal ion include alkali metals and alkaline earth metals such as Li, Na, K, Mg, Ca, Sr, and Ba, as well as Al, Sn, Sb, Ti, Mn, Fe, Ni, Cu, Zn, and Cd.

[0042] In the elastomer used in the present invention, the styrene-based elastomer is a block copolymer consisting of an aromatic vinyl compound-based polymer block such as styrene and a conjugated diene-based polymer block, and a block copolymer having at least one aromatic vinyl compound-based polymer block and at least one conjugated diene-based polymer block is used. In addition, the above block copolymer may have an unsaturated bond in the conjugated diene-based polymer block hydrogenated.

[0043] The aromatic vinyl compound polymer block is a polymer block mainly composed of structural units derived from an aromatic vinyl compound. Examples of aromatic vinyl compounds include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,6-dimethylstyrene, vinylnaphthalene, vinylanthracene, 4-propylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, and 4-(phenylbutyl)styrene. The aromatic vinyl compound polymer block may have structural units composed of one or more of the above-mentioned monomers, and may have structural units composed of a small amount of other unsaturated monomers.

[0044] The conjugated diene polymer block is a polymer block formed from one or more conjugated diene compounds such as 1,3-butadiene, chloroprene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 4-methyl-1,3-pentadiene, and 1,3-hexadiene, and in the hydrogenated aromatic vinyl compound / conjugated diene block copolymer, a part or all of the unsaturated bonds in the conjugated diene polymer block are saturated by hydrogenation. Here, the distribution in the polymer block mainly composed of conjugated diene may be random, tapered, partially block-like, or any combination thereof.

[0045] The molecular structure of the aromatic vinyl compound-conjugated diene block copolymer and its hydrogenated product may be linear, branched, radial, or any combination thereof. Among them, in the semi-aromatic polyamide resin composition of the present invention, the aromatic vinyl compound-conjugated diene block copolymer and / or its hydrogenated product are preferably one or more of a diblock copolymer in which one aromatic vinyl compound polymer block and one conjugated diene polymer block are linearly bonded, a triblock copolymer in which three polymer blocks are linearly bonded in the order of an aromatic vinyl compound polymer block, a conjugated diene polymer block, and an aromatic vinyl compound polymer block, and a hydrogenated product thereof, such as an unhydrogenated or hydrogenated styrene-butadiene copolymer, an unhydrogenated or hydrogenated styrene-isoprene copolymer, an unhydrogenated or hydrogenated styrene-isoprene-styrene copolymer, an unhydrogenated or hydrogenated styrene-butadiene-styrene copolymer, an unhydrogenated or hydrogenated styrene-isoprene-butadiene-styrene copolymer, an unhydrogenated or hydrogenated styrene-ethylene-butadiene-styrene block copolymer, etc.

[0046] The toughness improver (C) used in the present invention is preferably modified with a carboxylic acid and / or a derivative thereof. By modifying with these components, a functional group having affinity with the semi-aromatic polyamide resin (A) can be introduced into the molecule, and compatibility with the semi-aromatic polyamide resin (A) can be improved. Examples of the functional group having affinity with the semi-aromatic polyamide resin (A) include a carboxylic acid group, a carboxylic anhydride group, a carboxylic ester group, a carboxylic acid metal base, a carboxylic acid imide group, a carboxylic acid amide group, and an epoxy group. It is particularly preferable that the toughness improver (C) is at least one of an (ethylene and / or propylene)-α-olefin copolymer and a styrene-ethylene-butylene-styrene block copolymer modified with a carboxylic acid and / or a derivative thereof.

[0047] Examples of compounds that can improve the affinity with the semi-aromatic polyamide resin (A) include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, methyl maleic acid, methyl fumaric acid, mesaconic acid, citraconic acid, glutaconic acid, cis-4-cyclohexene-1,2-dicarboxylic acid, endobicyclo[2.2.1]-5-heptene-2,3-dicarboxylic acid, and metal salts of these carboxylic acids, monomethyl maleate, monomethyl itaconate, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and hydroxyethyl acrylate. Examples of the monomer units include methyl methacrylate, 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, aminoethyl methacrylate, dimethyl maleate, dimethyl itaconate, maleic anhydride, itaconic anhydride, citraconic anhydride, endo-bicyclo-[2.2.1]-5-heptene-2,3-dicarboxylic anhydride, maleimide, N-ethylmaleimide, N-butylmaleimide, N-phenylmaleimide, acrylamide, methacrylamide, glycidyl acrylate, glycidyl methacrylate, glycidyl ethacrylate, glycidyl itaconate, and glycidyl citraconate.

[0048] The amount of the toughness improver (C) used in the present invention must be 2 to 30 parts by mass relative to 100 parts by mass of the semi-aromatic polyamide (A). In addition, it is preferably 2 to 28 parts by mass, more preferably 2 to 25 parts by mass, and even more preferably 3 to 25 parts by mass. By setting the amount of the toughness improver (C) within the above range, excellent metal plating adhesion can be imparted, and high tensile elongation can be imparted, and cracks during molding and actual use can be suppressed. When the amount of the toughness improver (C) is below the above lower limit, metal plating adhesion may be insufficient, and cracks may occur during molding and actual use. When the amount of the toughness improver (C) is above the above upper limit, the heat resistance and deformation of the semi-aromatic polyamide resin composition may be impaired, and deformation of the molded product in the solder reflow process and deformation during actual use may occur. In the semi-aromatic polyamide resin composition of the present invention, the amount of the toughness improver is the content in the semi-aromatic polyamide resin composition as it is.

[0049] The semi-aromatic polyamide resin composition of the present invention is one in which the inorganic filler (B) is blended in a predetermined blending amount with the semi-aromatic polyamide resin (A) as described above, forming irregularities on the surface of the molded article after etching, and improving the metal plating adhesion by the mechanical bonding effect, and further blending a toughness improver (C) can be used to achieve even better metal plating adhesion. It is presumed that blending the toughness improver provides a mechanical bonding effect due to the irregularities at the interface between the metal plating and the semi-aromatic polyamide resin composition, and the viscosity of the semi-aromatic polyamide resin composition acts to achieve excellent metal plating adhesion.

[0050] The semi-aromatic polyamide resin composition of the present invention is obtained by blending a predetermined amount of inorganic filler (B) into the semi-aromatic polyamide resin (A) as described above, and further blending a predetermined amount of toughness improver (C) therein. This makes it possible to achieve high tensile elongation that is difficult to achieve in a system in which only inorganic fillers are blended.

[0051] The semi-aromatic polyamide resin composition of the present invention can contain various additives used in conventional polyamide resin compositions within the range that does not impair the properties of the composition. Examples of additives include stabilizers, release agents, sliding property improvers, colorants, plasticizers, crystal nucleating agents, polyamides different from the semi-aromatic polyamide resin (A), and thermoplastic resins other than polyamides. The possible blending amounts of these components in the semi-aromatic polyamide resin composition are as described below, but the total of these components is preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less in the semi-aromatic polyamide resin composition.

[0052] Examples of the stabilizer include organic antioxidants such as hindered phenol antioxidants, sulfur antioxidants, and phosphorus antioxidants, heat stabilizers, light stabilizers such as hindered amines, benzophenones, and imidazoles, ultraviolet absorbers, metal deactivators, and copper compounds. Examples of the copper compound include copper salts of organic carboxylic acids such as cuprous chloride, cuprous bromide, cuprous iodide, cupric chloride, cupric bromide, cupric iodide, cupric phosphate, cupric pyrophosphate, copper sulfide, copper nitrate, and copper acetate. In addition, it is preferable to contain an alkali metal halide compound as a component other than the copper compound, and examples of the alkali metal halide compound include lithium chloride, lithium bromide, lithium iodide, sodium fluoride, sodium chloride, sodium bromide, sodium iodide, potassium fluoride, potassium chloride, potassium bromide, and potassium iodide. These additives may be used alone or in combination of several types. The amount of stabilizer to be added may be selected optimally, but it is possible to add up to 5 parts by mass per 100 parts by mass of the semi-aromatic polyamide resin (A).

[0053] Examples of the release agent include long-chain fatty acids or their esters or metal salts, amide compounds, polyethylene wax, silicone, and polyethylene oxide. As the long-chain fatty acid, those having 12 or more carbon atoms are particularly preferable, and examples thereof include stearic acid, 12-hydroxystearic acid, behenic acid, and montanic acid, and the carboxylic acid may be partially or entirely esterified with monoglycol or polyglycol, or may form a metal salt. Examples of the amide compounds include ethylene bis-terephthalamide and methylene bis-stearylamide. These release agents may be used alone or as a mixture. The amount of the release agent to be added may be selected from the optimum amount, but it is possible to add up to 5 parts by mass per 100 parts by mass of the semi-aromatic polyamide resin (A).

[0054] The semi-aromatic polyamide resin composition of the present invention may be polymer-blended with a polyamide having a different composition from the semi-aromatic polyamide resin (A). The amount of the polyamide having a different composition from the semi-aromatic polyamide resin (A) added may be selected from the optimum amount, but it is possible to add up to 50 parts by mass per 100 parts by mass of the semi-aromatic polyamide resin (A).

[0055] The semi-aromatic polyamide resin composition of the present invention may contain thermoplastic resins other than polyamide. Examples of polymers other than polyamide include polyphenylene sulfide (PPS), liquid crystal polymer (LCP), aramid resin, polyetheretherketone (PEEK), polyetherketone (PEK), polyetherimide (PEI), thermoplastic polyimide, polyamideimide (PAI), polyetherketoneketone (PEKK), polyphenylene ether (PPE), polyethersulfone (PES), polysulfone (PSU), polyarylate (PAR), polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polycarbonate (PC), polyoxymethylene (POM), polypropylene (PP), polyethylene (PE), polymethylpentene (TPX), polystyrene (PS), polymethylmethacrylate, acrylonitrile-styrene copolymer (AS), and acrylonitrile-butadiene-styrene copolymer (ABS). These thermoplastic resins can be blended in a molten state by melt kneading, but the thermoplastic resins may be made fibrous or granular and dispersed in the polyamide resin composition of the present invention. The amount of the thermoplastic resin to be added can be selected from the optimum amount, but it is possible to add up to 50 parts by mass per 100 parts by mass of the semi-aromatic polyamide resin (A).

[0056] When a thermoplastic resin other than the aromatic polyamide resin (A) is added to the semi-aromatic polyamide resin composition of the present invention, it is preferable that a reactive group capable of reacting with the polyamide is copolymerized, and the reactive group is a group capable of reacting with the amino group, carboxyl group, and main chain amide group, which are the terminal groups of the polyamide resin.Specific examples of the reactive group include a carboxylic acid group, an acid anhydride group, an epoxy group, an oxazoline group, an amino group, and an isocyanate group, and among them, an acid anhydride group has the highest reactivity.

[0057] The semi-aromatic polyamide resin composition of the present invention can be produced by blending the above-mentioned components by a conventionally known method, for example, by adding each component during the polycondensation reaction of the semi-aromatic polyamide resin (A), by dry blending the semi-aromatic polyamide resin (A) with other components, or by melt-kneading each component using a twin-screw extruder.

[0058] The semi-aromatic polyamide resin composition of the present invention can be molded into a molded article by a known molding method such as injection molding. When a molded article is manufactured using the semi-aromatic polyamide resin composition of the present invention, the mold temperature in injection molding is preferably 180°C or less, more preferably 170°C or less, even more preferably 160°C or less, and particularly preferably 150°C or less. If the mold temperature exceeds the upper limit, molding defects such as the molded article remaining in the mold may occur. There is no particular limit to the lower limit of the mold temperature, but from the viewpoint of the fluidity of the resin, the appearance of the molded article, and the suppression of dimensional change in the actual use environment, it is preferably 50°C or more, more preferably 70°C or more, even more preferably 100°C or more, and particularly preferably 120°C or more.

[0059] The semi-aromatic polyamide resin composition of the present invention can be used as a metal-plated molded article obtained by plating the surface of a molded article obtained by using the composition. The metal-plated molded article has excellent metal plating adhesion, low water absorption, and solder reflow resistance compared to conventional metal-plated molded articles.

[0060] The method for producing a metal-plated molded body using the semi-aromatic polyamide resin composition of the present invention is not particularly limited, and can be produced by known techniques. For example, the catalyst accelerator method in which the surface is roughened by chemical etching using chromic acid, permanganic acid, hydrochloric acid, etc., and then the roughened surface is used to perform steps such as neutralization, catalyst application, activation, electroless plating, acid activation, and electroplating in order, or the direct plating method in which the electroless plating step in the catalyst accelerator method is omitted, the surface is modified by ultraviolet light or a laser light having a specific wavelength, and then the modified surface is used to perform steps such as catalyst application, activation, electroless plating, acid activation, and electroplating in order, or the direct plating method in which the electroless plating step in the catalyst accelerator method is omitted, or the like, can be mentioned. The etching and metal plating can be performed on the entire surface of the molded body to be plated, or on a part of it.

[0061] The thickness of the metal plating of the metal-plated molded article using the semi-aromatic polyamide resin composition of the present invention may be selected optimally, but is preferably 0.5 to 200 μm, more preferably 1 to 150 μm.

[0062] Metal-plated molded articles using the semi-aromatic polyamide resin composition of the present invention have excellent metal adhesion due to the filler and toughness improver blended in the semi-aromatic polyamide resin composition.

[0063] The metal plating peel strength of the metal-plated molded article using the semi-aromatic polyamide resin composition of the present invention is measured by the method described in the following Examples section. The metal plating peel strength is an item related to the good plating properties of the semi-aromatic polyamide resin composition of the present invention, and the metal plating peel strength must be 4.0 N / cm or more, and is preferably 5.0 N / cm or more. In addition, in order to suppress the occurrence of poor adhesion such as lifting or peeling of the metal plating under the usage environment, it is advantageous to have a higher metal plating peel strength, and it is more preferable that it is 6.0 N / cm or more, and this metal plating peel strength can be achieved in the present invention. The metal plating peel strength is more preferably 6.5 N / cm or more. If the metal plating peel strength is below the above lower limit, the adhesion between the semi-aromatic polyamide resin composition and the metal plating is low, and lifting or peeling of the metal plating may occur.

[0064] The tensile elongation of the molded article for metal plating using the semi-aromatic polyamide resin composition of the present invention is measured by the method described in the Examples section below. The tensile elongation is an item related to the molding processability of the semi-aromatic polyamide resin composition of the present invention and the durability of the product during actual use, and the tensile elongation must be 1.5% or more, and is preferably 1.7% or more. If the tensile elongation is below the lower limit, cracks may occur during molding or during actual use.

[0065] Metal-plated molded articles using the semi-aromatic polyamide resin composition of the present invention can be used for various applications such as automobile parts, electric and electronic parts, office automation equipment parts, and electromagnetic wave shielding parts, taking advantage of their excellent metal plating adhesion. EXAMPLES

[0066] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The measured values ​​described in the examples were measured by the following methods.

[0067] (1) Terminal amino group concentration (AEG), terminal carboxyl group concentration (CEG) Semi-aromatic polyamide resin (A) is dissolved in a solvent of deuterated chloroform (CDCl3) / hexafluoroisopropanol (HFIP) = 1 / 1 (volume ratio), and polyformic acid is added dropwise, 1 The concentration of each end group was measured by H-NMR.

[0068] (2) Relative Viscosity (RV) 0.25 g of the semi-aromatic polyamide resin was dissolved in 25 ml of 96% sulfuric acid, and the viscosity was measured at 20° C. using an Ostwald viscometer.

[0069] (3) Melting point (Tm) A semi-aromatic polyamide resin dried under reduced pressure at 105°C for 15 hours was weighed out in an aluminum pan (SII Nanotechnology, part number 170421S) in an amount of 10 mg and sealed with an aluminum lid (SII Nanotechnology, part number 170420) to prepare a measurement sample. The sample was then heated from room temperature at 20°C / min using a high-sensitivity differential scanning calorimeter DSC7020 (SII Nanotechnology), held at 350°C for 3 minutes, and then the measurement sample pan was removed and immersed in liquid nitrogen for rapid cooling. The sample was then removed from the liquid nitrogen and left at room temperature for 30 minutes, after which it was heated again from room temperature at 20°C / min using a high-sensitivity differential scanning calorimeter DSC7020 (SII Nanotechnology), held at 350°C for 3 minutes. The peak temperature of the endothermic heat generated by melting during the temperature rise was taken as the melting point (Tm).

[0070] (4) 80℃95%RH equilibrium water absorption rate Using a Toshiba Machine injection molding machine EC-100, the cylinder temperature was set to the melting point of the resin + 20 ° C, the mold temperature was set to 140 ° C, and a flat plate with a length of 100 mm, a width of 100 mm, and a thickness of 1 mm was injection molded to prepare a test piece for evaluation. After annealing the test piece for 2 hours in an atmosphere of 150 ° C, the mass was measured, and the mass at this time was taken as the mass when dried. Furthermore, the annealed test piece was left to stand for 1000 hours in an atmosphere of 85 ° C and 95% RH (relative humidity), and then the mass was measured, and the mass at this time was taken as the mass when saturated with water absorption. The 80 ° C and 95% RH equilibrium water absorption rate was calculated from the mass when saturated with water absorption and when dried measured by the above-mentioned method using the following formula. 80℃95%RH Equilibrium water absorption rate (%) = {(mass at saturation - mass when dry) / mass when dry mass}×100

[0071] (5) Tensile elongation A multipurpose test piece (ISO3167) was prepared in accordance with ISO 294-1 using a Toshiba Machine EC-100 injection molding machine, with the cylinder temperature set to the resin melting point + 20°C and the mold temperature set to 140°C. The prepared test piece was used to evaluate tensile elongation in accordance with ISO 527-1,2.

[0072] (6) Metal plating peel strength Using a Toshiba Machine injection molding machine EC-100, the cylinder temperature was set to the melting point of the resin + 20°C, the mold temperature was set to 140°C, and a flat plate with a length of 100 mm, width of 100 mm, and thickness of 2 mm was injection molded to prepare a test specimen for evaluation. The obtained test specimen was wiped with isopropyl alcohol, and then degreased at 60°C for 3 minutes using 50g / l OPC-250 cleaner (manufactured by Okuno Pharmaceutical Co., Ltd.). The test specimen was then immersed in a 70°C chromic acid solution consisting of 400g / l chromic acid, 200ml / l concentrated sulfuric acid, and 0.3g / l Top Shut (manufactured by Okuno Pharmaceutical Co., Ltd.) for 5 minutes to perform surface treatment. The surface-treated test specimen was acid washed at room temperature for 3 minutes with a 5% aqueous solution of 38% hydrochloric acid, and then immersed in a treatment solution consisting of 200ml / l B-200 Neutralizer (manufactured by Okuno Pharmaceutical Co., Ltd.) adjusted to 45°C for 5 minutes. Next, the specimen was immersed for 4 minutes in a treatment solution consisting of a tin-palladium complex salt solution (A30 Catalyst, manufactured by Okuno Pharmaceutical Co., Ltd.), hydrochloric acid, and water (volume ratio = 1:1:5) prepared at 25°C (catalyzing). After that, the specimen was immersed for 4 minutes in a 10% aqueous solution of 38% hydrochloric acid prepared at 50°C (accelerating), and then immersed for 10 minutes in an electroless nickel plating solution consisting of TMP Chemical Nickel A and B solutions (manufactured by Okuno Pharmaceutical Co., Ltd.) and water (volume ratio = 1:1:4) prepared at 40°C, forming a nickel plating layer of about 1 μm on the surface of the specimen, and further electrolytic copper plating was applied to form a copper plating layer. A strip specimen measuring 100 mm in length, 10 mm in width, and 2 mm in thickness was cut out from the obtained metal-plated specimen to be used as a peel strength evaluation specimen. The metal plating peel strength was measured using the prepared peel strength evaluation specimen in accordance with the JIS H8630 90-degree peel strength test method.

[0073] (7) Metal-plated appearance Using a Toshiba Machine injection molding machine EC-100, the cylinder temperature was set to the melting point of the resin + 20°C, the mold temperature was set to 140°C, and a flat plate with a length of 100 mm, width of 100 mm, and thickness of 2 mm was injection molded to prepare a test specimen for evaluation. The obtained test specimen was wiped with isopropyl alcohol, and then degreased at 60°C for 3 minutes using 50g / l OPC-250 cleaner (manufactured by Okuno Pharmaceutical Co., Ltd.). The test specimen was then immersed in a 70°C chromic acid solution consisting of 400g / l chromic acid, 200ml / l concentrated sulfuric acid, and 0.3g / l Top Shut (manufactured by Okuno Pharmaceutical Co., Ltd.) for 5 minutes to perform surface treatment. The surface-treated test specimen was acid washed at room temperature for 3 minutes with a 5% aqueous solution of 38% hydrochloric acid, and then immersed in a treatment solution consisting of 200ml / l B-200 Neutralizer (manufactured by Okuno Pharmaceutical Co., Ltd.) adjusted to 45°C for 5 minutes. Next, the test piece was immersed for 4 minutes in a treatment solution consisting of a tin-palladium complex salt solution (A30 Catalyst, manufactured by Okuno Pharmaceutical Co., Ltd.), hydrochloric acid, and water (volume ratio = 1:1:5) prepared at 25°C (catalyzing). After that, the test piece was immersed for 4 minutes in a 10% aqueous solution of 38% hydrochloric acid prepared at 50°C (accelerating), and then immersed for 10 minutes in an electroless nickel plating solution consisting of TMP Chemical Nickel A and B solutions (manufactured by Okuno Pharmaceutical Co., Ltd.) and water (volume ratio = 1:1:4) prepared at 40°C, forming a nickel plating layer of about 1 μm on the surface of the test piece, and further electrolytic copper plating was applied to form a copper plating layer. The appearance of the obtained metal-plated test piece was observed, and the appearance was evaluated based on the presence or absence of lifting of the metal plating. ○: No lifting of metal plating ×: Metal plating is peeling off

[0074] (8) Solder reflow resistance Using a Toshiba Machine injection molding machine EC-100, the cylinder temperature was set to the melting point of the resin + 20°C, the mold temperature was set to 140°C, and a UL combustion test piece with a length of 127 mm, width of 12.6 mm, and thickness of 0.8 mm was injection molded to prepare a test piece. The test piece was left in an atmosphere of 85°C and 85% RH (relative humidity) for 72 hours. The test piece was preheated in an air reflow furnace (Atec AIS-20-82C) by raising the temperature from room temperature to 150°C over 60 seconds, and then preheated to 190°C at a heating rate of 0.5°C / min. The temperature was then raised to a specified set temperature at a rate of 100°C / min, held at the specified temperature for 10 seconds, and then cooled. The set temperature was increased in 5°C increments from 240°C, and the highest set temperature at which no swelling or deformation of the surface occurred was taken as the reflow heat resistance temperature and used as an index of solder heat resistance. ○: Reflow heat resistance temperature is 260℃ or higher ×: Reflow heat resistance temperature is less than 260℃

[0075] In this example, semi-aromatic polyamide resin (A) was synthesized by the following method or a commercially available product. The physical properties of each semi-aromatic polyamide resin (A) are shown in Table 1.

[0076] [Table 1]

[0077] <Synthesis Example 1: Semi-aromatic polyamide resin (A1)> 8.55 kg of 1,6-hexamethylenediamine, 12.25 kg of terephthalic acid, 8.00 kg of 11-aminoundecanoic acid, 9 g of sodium hypophosphite as a catalyst, 140 g of acetic acid as a terminal regulator, and 16.20 kg of ion-exchanged water were charged into a 50-liter autoclave, pressurized from normal pressure to 0.05 MPa with N2, released the pressure, and returned to normal pressure. This operation was repeated three times to replace with N2, and then the mixture was uniformly dissolved at 135°C and 0.3 MPa under stirring. The solution was then continuously fed by a liquid feed pump, heated to 240°C by a heating pipe, and heated for 1 hour. The reaction mixture was then fed to a pressurized reactor and heated to 290°C, and a portion of the water was distilled off so as to maintain the internal pressure of the reactor at 3MPa, to obtain a low-order condensate. The low-order condensate was then fed directly to a twin-screw extruder (screw diameter 37 mm, L / D=60) while maintaining the molten state, and polycondensation was carried out under molten conditions while the resin temperature was kept at 335°C and water was removed from three vents, to obtain a semi-aromatic polyamide resin (A1). The obtained semi-aromatic polyamide resin (A1) was composed of 65.1 mol% of structural units consisting of 1,6-hexamethylenediamine and terephthalic acid, and 34.9 mol% of structural units consisting of 11-aminoundecanoic acid, and had a relative viscosity of 2.1, a melting point of 314°C, AEG 30 eq / ton, and CEG 140 eq / ton. The ratio of constituent monomers of polyamide resin was the same as that of AEG and CEG measurements. 1 This was confirmed by H-NMR.

[0078] <Synthesis Example 2: Semi-aromatic polyamide resin (A2)> According to the method described in Example 1 of JP-A-7-228689, a semi-aromatic polyamide resin consisting of terephthalic acid units, 1,9-nonanediamine units and 2-methyl-1,8-octanediamine units (molar ratio of 1,9-nonanediamine units:2-methyl-1,8-octanediamine units is 85:15) was synthesized (benzoic acid was used as an end-capping agent). The obtained semi-aromatic polyamide resin (A2) was composed of 85.2 mol% of constituent units consisting of 1,9-nonanediamine and terephthalic acid and 14.8 mol% of constituent units consisting of 2-methyl-1,8-octanediamine and terephthalic acid, and had a relative viscosity of 2.1, a melting point of 286°C, an AEG of 13 eq / ton and a CEG of 50 eq / ton. The constituent monomer ratio of the polyamide resin was, as in the AEG and CEG measurements, 1 This was confirmed by H-NMR.

[0079] The present examples were carried out using semi-aromatic polyamide resin compositions prepared as exemplified below.

[0080] The components and mass ratios (parts by mass) shown in Tables 2 and 3 were melt-kneaded at the melting point of each polyamide raw material +20°C using a twin-screw extruder STS-35 manufactured by Coperion Co., Ltd. to obtain semi-aromatic polyamide resin compositions of Examples 1 to 11 and Comparative Examples 1 to 5. The raw materials used in producing the semi-aromatic polyamide resin compositions are as follows. The release agent and stabilizer used as other additives were used in a mass ratio of 1:5.

[0081] Semi-aromatic polyamide resin (A1): Semi-aromatic polyamide resin prepared according to Synthesis Example 1 above Semi-aromatic polyamide resin (A2): Semi-aromatic polyamide resin prepared according to Synthesis Example 2 above Semi-aromatic polyamide resin (A3): PA6T / 6 (BASF Ultramide(R) KR4351, Tm=290°C)

[0082] Inorganic filler (B1): Calcined kaolin (BASF, Translink(R) 445, surface-treated, average particle size 1.4 μm) Inorganic filler (B2): Calcined kaolin (BASF, Satintone(R)5HB, no surface treatment, average particle size 0.8μm) Inorganic filler (B3): Fibrous wollastonite (NYCO, NYGLOS(R)8, surface-treated)

[0083] Toughness improver (C1): Maleic anhydride modified styrene-ethylene-butylene-styrene block copolymer (Asahi Kasei Corporation, Tuftec(R) M1943) Toughness improver (C2): Maleic anhydride modified ethylene-butene copolymer (Mitsui Chemicals, Toughmer(R) MH7020) Toughness improver (C3): Maleic anhydride modified propylene-butene copolymer (Mitsui Chemicals, Toughmer(R) MP0620) Toughness improver (C4): Ethylene-acrylic ester-maleic anhydride copolymer (Arkema, Bondine(R)AX-8390)

[0084] Release agent: Magnesium stearate Stabilizer: Pentaerythrityl tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (Irganox1010, manufactured by Chiba Speciality Chemicals)

[0085] [Table 2]

[0086] [Table 3]

[0087] <Examples 1 to 11 and Comparative Examples 1 to 5> As is clear from Table 2, Examples 1 to 11 exhibit excellent tensile elongation, metal plating peel strength, and metal plating appearance, and also have reflow solder resistance, and are therefore excellent in properties. Furthermore, Examples 1 to 7 and 9 exhibit particularly excellent metal plating peel strength, and are therefore excellent in properties. On the other hand, Table 3 shows that Comparative Examples 1 and 2 have good metal plating appearance and reflow solder resistance, but because they do not contain the toughness improver (C), they have low tensile elongation and metal plating peel strength is also lower than that of the Examples, and are insufficient in suppressing poor plating adhesion under the usage environment. Comparative Example 3 has good tensile elongation and reflow solder resistance, but because it does not contain the inorganic filler (B), it is inferior in metal plating peel strength and metal plating appearance. Comparative Example 4 uses a semi-aromatic polyamide (PA9T / M8T) different from those used in Examples 1 to 10, and although it has good reflow solder resistance, it has low tensile elongation and metal plating peel strength that is also lower than those in the Examples, and is insufficient in suppressing poor plating adhesion under the usage environment. Comparative Example 5 uses a semi-aromatic polyamide (PA6T / 6) different from those used in Examples 1 to 11, and it has low tensile elongation and metal plating peel strength that is also lower than those in the Examples, and is insufficient in suppressing poor plating adhesion under the usage environment, as well as a high saturated water absorption rate at 80°C / 95% RH, and therefore is poor in reflow solder resistance. [Industrial Applicability]

[0088] The semi-aromatic polyamide resin composition of the present invention, by blending an inorganic filler and a toughness improver in addition to the composition of a semi-aromatic polyamide resin, exhibits good metal plating adhesion and plating appearance and also satisfies solder reflow resistance, and can advantageously produce molded articles requiring metal plating on an industrial scale.

Claims

1. A semi-aromatic polyamide resin composition for metal-plated molded articles, which contains 10 to 200 parts by mass of an inorganic filler (B) and 2 to 30 parts by mass of a toughness improver (C) per 100 parts by mass of a semi-aromatic polyamide resin (A), and which satisfies the following (a) and (b) (excluding those containing a laser direct structuring (LDS) additive): (a) A melting point (Tm) measured by differential scanning calorimetry (DSC) of 280° C. or higher (b) Equilibrium water absorption at 80°C and 95% RH is 3.5% or less

2. The semi-aromatic polyamide resin composition according to claim 1, wherein the toughness improver (C) is at least one selected from the group consisting of olefin-based copolymers and styrene-based elastomers.

3. The semi-aromatic polyamide resin composition according to claim 2, wherein the olefin-based copolymer is at least one selected from the group consisting of (ethylene and / or propylene) / α-olefin-based copolymers and (ethylene and / or propylene) / (α,β-unsaturated carboxylic acid and / or unsaturated carboxylic acid ester)-based copolymers.

4. 4. The semi-aromatic polyamide resin composition according to claim 2, wherein the styrene-based elastomer is a styrene-ethylene-butylene-styrene block copolymer.

5. The semi-aromatic polyamide resin composition according to any one of claims 1 to 4, wherein the inorganic filler (B) comprises an aluminum silicate or a calcium silicate.

6. A metal-plated molded article using the semi-aromatic polyamide resin composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation of silver halide color photographic sensitive material

    JP1986090154A

  • Anti-rolling hydrofoil device with safety device

    JP1996011782A

  • Polyamide, polyamide composition, and their production methods

    JP2001247673A

  • Resin composition for metal vapor deposition, metal-deposited molded product and method for producing the metal-deposited molded product

    JP2006131821A

  • Resin composition exhibiting excellent heat resistance

    JP2007154110A